Henoch-Schönlein purpura in children: A cross sectional study - Karaaslan, Fatih; Karaaslan, Betul Gemici; Dag, Huseyin; Sazak, Soner; Turkkan, Emine; Yılmaz, Bilal; Midillioglu, Gulsen Kose (Indian Journal of Child Health, 2019)
Background: Henoch-Schönlein purpura (HSP) is a leukocytoclastic vasculitis with small vessel involvement and mainly affects the skin as well as joints, the gastrointestinal system (GIS), kidneys, and, more rarely, other organs. Objective: The objective of this study was to evaluate the sociodemographic characteristics, and clinical and laboratory findings of patients diagnosed with HSP. Materials and Methods: This was a retrospective study done to find out the sociodemographic data, clinical, laboratory findings, and treatment information of patients diagnosed with HSP and was admitted to the Pediatric Clinic of a tertiary care hospital between January 1, 2008, and August 31, 2013. The data were obtained from the hospital’s data processing system. HSP cases were validated according to EULAR/PRINTO/PRES criteria. Mean standard deviation, median, lowest and highest, frequency, and ratio values were used in the descriptive statistics of the data. Results: The study included 85 patients between the ages of 2 and 16 years, wherein 49 patients (57.6%) were male and 36 (42.4%) were female. The mean age was 9.9±3.3 years and 53 patients (62.4%) were under 10 years of age. The most common precipitating factor was upper respiratory tract infections. Purpura was the only symptom observed in all the patients and joint involvement was the second most common symptom (60%). GIS involvement was observed in 46 patients (58.8%) and intussusception was observed in one patient. Nine patients (10.6%) had renal involvement with mild nephropathy. The most frequently observed laboratory findings were increased C-reactive protein (47%) and leukocytosis (31%). Conclusion: HSP is commonly seen in children and leads to life-threatening complications in a minority of patients. Whole patients with GIS and renal involvement should be examined and monitored to assess the severity of the disease and any complications.